Novel compound heterozygous CCDC40 mutations in a familial case of primary ciliary dyskinesia - Zhao, Liqing; Huang, Suqiu; Wei, Wei; Zhang, Bingyao; Shi, Wenxiang; Liang, Yongzhou; Xu, Rang; Wu, Yurong (Frontiers in Pediatrics, 2022)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by motile ciliary dysfunction and impaired ultrastructure. Despite numerous studies, the genetic basis for about 30% of PCD cases remains to be elucidated. Here, we present the identification and functional analysis of two novel mutations in the gene encoding coiled-coil domain-containing protein 40 (CCDC40), which are found in a familial case of PCD. These novel CCDC40 mutations, NM_017950.4: c.2236-2delA and c.2042_2046delTCACA, NP_060420.2: p.(Ile681fs), were identified by whole-exome sequencing (WES). Sanger sequencing was then performed to confirm the WES results and determine the CCDC40 gene sequences of the proband’s parents. The c.2042_2046delTCACA mutation disrupts the reading frame of the protein and is therefore predicted to produce a non-functional protein. Using a minigene assay with the pcDNA3.1(+) plasmid, we further investigated the potential pathogenic effects of the c.2236-2delA mutation and found that this mutation leads to formation of a truncated protein via splicing disruption. Thus, in summary, we identified two mutations of the CCDC40 gene that can be considered pathogenic compound heterozygous mutations in a case of familial PCD, thereby expanding the known mutational spectrum of the CCDC40 gene in this disease.